2020
DOI: 10.1144/qjegh2020-023
|View full text |Cite
|
Sign up to set email alerts
|

Developing conceptual models for the recognition of coseismic landslides hazard for shallow crustal and megathrust earthquakes in different mountain environments – an example from the Chilean Andes

Abstract: Landslides represent the most frequent geological hazard in mountainous environments. Most notably, landslides are a major source of fatalities and damage related to strong earthquakes. The main aim of this research is to show through three-dimensional engineer-friendly computer drawings, different mountain environments where coseismic landslides could be generated during shallow crustal and megathrust earthquakes in the Andes of central Chile. We have determined topographic, geomorphological, geological and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…After mapping the geographic distribution of submarine landslides reported by Rincon et al, 2021 (Figure 2), its relation with ground conditions including seafloor geomorphology, slope degree, and faults presence, was analyzed. For this purpose, we present bathymetric images and conceptual models (Serey A et al, 2020) to condense the main geomorphological features observed on the seafloor. In addition, looking for evidence connecting gas hydrate dissociation and submarine landslides, we analyzed the position of landslide glides concerning the Bottom Simulator Reflector (BSR) (McIver, 1982;Kayen and Lee, 1993;Kvenvolden, 1993;Miniert et al, 2005;Talling et al, 2014;Mountjoy, 2014;Wu et al, 2018).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…After mapping the geographic distribution of submarine landslides reported by Rincon et al, 2021 (Figure 2), its relation with ground conditions including seafloor geomorphology, slope degree, and faults presence, was analyzed. For this purpose, we present bathymetric images and conceptual models (Serey A et al, 2020) to condense the main geomorphological features observed on the seafloor. In addition, looking for evidence connecting gas hydrate dissociation and submarine landslides, we analyzed the position of landslide glides concerning the Bottom Simulator Reflector (BSR) (McIver, 1982;Kayen and Lee, 1993;Kvenvolden, 1993;Miniert et al, 2005;Talling et al, 2014;Mountjoy, 2014;Wu et al, 2018).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…1b; e.g. Serey et al, 2020). Therefore in the absence of absolute dates, the tectonic geomorphology constitutes important chronological support.…”
Section: N P R E S Smentioning
confidence: 99%
“…In Chile, landslides are one of the most common geological hazards, together with earthquakes, volcanic activity, and floods. The geological, geomorphological, tectonic, and climatic conditions of the country, characterized by the presence of the Andes Mountain Range on its eastern margin and the Coastal Mountain Range on its western margin, make it highly susceptible to the generation of mass movements such as landslides, rockfalls, flows, and falls [10]. Within 52 declared events in Chile, there have been a total of 1010 fatal victims caused by landslides, corresponding to 882 deaths and 128 people missing between 1928 and 2017 (90 years) [11].…”
Section: Introductionmentioning
confidence: 99%